Measuring state pre-event and post-event rumination in Social Anxiety Disorder: Psychometric properties of the Socially Anxious Rumination Questionnaire (SARQ). (August 2021) - Donohue, Hayley E.; Rapee, Ronald M.; Modini, Matthew; Norton, Alice R.; Abbott, Maree J.
Highlights: First study to assess the factor structure of the SARQ in a clinical SAD sample. One factor solutions demonstrated for the SARQ: Pre-event and SARQ: Post-event. The SARQ demonstrated good validity and reliability. The SARQ showed responsivity to treatment and clinical utility. SARQ assesses rumination in relation to a range of social threat tasks in SAD. Abstract: Cognitive models have consistently recognised pre-event and post-event rumination as maintaining factors in Social Anxiety Disorder (SAD). This study aimed to investigate the psychometric properties of a state-based measure of pre-event and post-event rumination in SAD: The Socially Anxious Rumination Questionnaire (SARQ), which was formerly known as the Thoughts Questionnaire. In particular, we examined the factor structure, internal consistency, test-retest reliability, construct validity, sensitivity to treatment response, clinical cut-off scores (relative to non-clinical participants), and associated test performance indicators of the SARQ. The sample comprised 505 adults with a principal diagnosis of SAD and 130 non-clinical controls. Pre-event and post-event rumination were assessed in relation to a three-minute impromptu speech. Results indicated single factors for the SARQ: Pre-event and SARQ: Post-event scales, along with excellent internal consistency, good test-retest reliability, sound sensitivity to cognitive-behavioural treatment response, and a clear ability to discriminate between individuals with a principal diagnosis of SAD and non-clinical controls. The findings justify the SARQ's use as a robust and reliable measure of state rumination for individuals with SAD that can be used both before and after encountering a social threat.